Principles of planning and development in the context of legislative changes - Domańska, Anna (Transformations of modern cities: Selected trends and instruments, 2022)
The dynamics of legislative changes seems to be gaining momentum over the last few years. These changes also concern the sphere of spatial planning law. The basic standards of spatial planning are set out in the Act of 27 March 2003 on spatial planning and development. This chapter is a reflection on the impact of specific regulations on the content and meaning of selected principles of spatial development law. With the current legislative policy, preferring ad hoc acts instead of stable legal norms, it is reasonable to ask about the significance of the principles of spatial planning and development provided for in the Spatial Planning and Development Act. These rules are used to determine certain directions of activities and enforce certain behaviors necessary to protect certain values, in particular spatial order and sustainable development. There is an increased activity of the legislator aimed at introducing many exceptions to the rules set out in the Act on spatial planning and development. The so-called special acts, which are intended to improve procedures and implement ad hoc goals desired by the legislator.